Facile Synthesis of Ladder‐Type Polyacenes with Perylene‐Fused‐Pyrene Structures. Issue 17 (8th August 2018) - Hu, Chaoying; Chen, Weiping; Yao, Haicui; Ren, Xiaojie; Zhang, Hailei; Zhao, Hongchi; Wu, Yonggang; Ba, Xinwu
Abstract: Ladder‐type polyacene (FP2) and model compounds (1c and 2c) with perylene‐fused‐pyrene structures are achieved in high yields by using a Pd(PPh3 )2 Cl2 ‐catalyzed Suzuki reaction followed by cyclization with FeCl3 . The obtained model compounds and polyacene display desirable solubility in commonly used solvents and high thermal stability. Fluorescence peak at 614 nm is observed in diluted CH2 Cl2 solution containing polyacene. Furthermore, the as‐prepared model compound (2c) and polyacene (FP2) are employed as acceptors in bulk‐heterojunction (BHJ) solar cells with PTB7‐Th as electrodonor cells. The 2c‐based solar cell demonstrates a power conversion efficiency of 3.25%. Abstract : Ladder‐type polyacene (FP2) and model compounds (1c and 2c) with perylene‐fused‐pyrene structures are acheived in high yields by using a Pd(PPh3 )2 Cl2 ‐catalyzed Suzuki reaction. Fluorescence peak at 614 nm is observed in diluted CH2 Cl2 solution containing polyacene. The model compound‐based solar cell demonstrates a power conversion efficiency of 3.25%.